Undiagnosed type B interrupted aortic arch without a patent ductus arteriosus identified during adolescence. (March 2019) - Burt, Jeremy R.; Grekoski, Vincent; Tissavirasingham, Fiona; Parente, Ryan; Garcia, Jorge
Abstract: Type B interrupted aortic arch without a patent ductus arteriosus or ventricular septal defect is extremely rare. We present a case of this congenital abnormality with the initial presentation at 15 years of age. Our case demonstrates the efficacy of CT angiography in diagnosing this condition in addition to characterizing the anatomy of collateral blood flow. Furthermore, this study provides updated imaging information on interrupted aortic arch without a patent ductus arteriosus and will guide physicians in selecting the appropriate diagnostic imaging modality to evaluate this condition. Highlights: CT angiography is the ideal imaging modality for diagnosing interrupted aortic arch without a patent ductus arteriosus or ventricular septal defect Type B interrupted aortic arch without a patent ductus arteriosus or ventricular septal defect is extremely rare Large collateral pathways develop in the setting of chronic interrupted aortic arch without a patent ductus arteriosus or ventricular septal defect